Towards clinical definitions of lower respiratory tract infection (LRTI) for research and primary care practice in Europe: an international consensus study. - Greene, G; Hood, K; Little, P; Verheij, T; Goossens, H; Coenen, S; Butler, C (2011)
AIMS: Antibiotic prescriptions for lower respiratory tract infection (LRTI) account for a large proportion of antibiotic consumption. Many of these prescriptions do not benefit patients and contribute to antibiotic resistance. Research to improve evidence-based management requires clear definitions of clinical entities. We aimed to generate definitions for common LRTIs that are applicable to clinical practice and low-intensity investigation research settings in European primary care. METHODS: Candidate definitions identified through a systematic review and a nominal group meeting were put to a Delphi panel of selected experts from Europe and the US over three rounds. The definitions achieving high consensus were then tested for face validity by an expert panel. RESULTS: 253 papers met our search criteria. The nominal group meeting generated highly-ranked definitions for two LRTIs. The Delphi panel considered five candidate definitions derived from the systematic review and nominal group meeting, and agreed upon definitions and open comments that the expert panel assessed for face validity. CONCLUSIONS: We combined empirical evidence with expert opinion for the development of a set of relevant clinical and research definitions for the four most common LRTIs presenting in general practice.